Polarisation of Islamic Scholars on the Legality of Cryptocurrency Usage as Currency - Buana, Andika Prawira; Rizki Ramadani; Aan Aswari; Zainuddin (Arena Hukum, 2024)
Cryptocurrency has become a key focus in the evolving landscape of virtual finance, sparking a divide among Islamic scholars. The debate centres on whether cryptocurrency should be considered permissible for transactions under Islamic law. This study explores the polarisation among scholars, some of whom permit cryptocurrency use while others prohibit it. Using normative legal research methods with statutory and conceptual approaches from an Islamic law perspective, the study draws on secondary data, including primary, secondary and tertiary legal materials. The findings reveal that some scholars oppose cryptocurrency due to its lack of intrinsic value and high volatility, which leads to gharar (uncertainty). Conversely, others argue that cryptocurrency can be permitted if limited to monetary functions and not for other purposes. The study concludes by recommending that, as cryptocurrency becomes increasingly prevalent, Islamic scholars should work to establish ijma’ (consensus) and qiyas (analogical reasoning) to form a clear basis for determining its permissibility according to Islamic principles.